Solubility and effective enzymatic hydrolysis of oat globulins - Pia Laine; Loponen, Jussi (MTT, 2004)
Enzymatic hydrolysis of proteins is used to improve nutritional and functional properties of many foods. The desired degree of hydrolysis (DH) depends on food application. Effective hydrolysis requires optimal hydrolysis conditions for both the enzyme and the substrate protein. This study aimed to hydrolyze the oat globulins (OG) effectively under different conditions. Our first goal was to maximise the OG solubility and then to hydrolyze OG under optimised conditions. The solubility of isolated OG in Na-phosphate solutions containing 0 1 M NaCl was determined. Globulins were subjected to single-enzyme hydrolysis with either subtilisin, thermolysin or pepsin. In addition, OG were degraded in two-stage hydrolysis first with pepsin and then either with subtilisin or thermolysin. The hydrolysates were analysed by SDS-PAGE and DH was quantified with the OPA method. The solubility of OG increased when NaCl was added at pH 5 10. Under more acidic conditions the solubility, however, decreased with added NaCl. Solubility of OG was the lowest near its isoelectric point, whereas solubility was the highest at pH 2 3 with no added NaCl and at extremely alkaline conditions in all studied salt concentrations. The DH varied between 8 20% in single-enzyme hydrolysis. The degradation of OG became more effective in combined hydrolysis with pepsin and subtilisin (DH 42%) or pepsin and thermolysin (DH 30%). The present study demonstrates that solubility of OG was strongly dependent on pH and NaCl concentration and it was shown that pepsin, subtilisin and thermolysin degraded OG under optimized conditions. Thus, by optimisation of the conditions for both the enzyme and the substrate protein, effective hydrolysis may be obtained.
Keywords: Ka; oat; globulin; hydrolysis; solubility